Tuneable reduction of CO2 – organocatalyzed selective formylation and methylation of amines - Ren, Changyue; Terazzi, Constanza; Werner, Thomas (Green Chemistry)
The selective N -formylation and N -methylation of amines with carbon dioxide (CO 2 ) catalyzed by methyltriphenylphosphonium methylcarbonate and tuned by polymethylhydrosiloxane or trimethoxysilane as reducing agents is reported.
Keywords: T1; T2; CSSD

Phosphonium-Salt-Catalyzed N-Methylation and N-Formylation of Amines with CO2 - Ren, Changyue; Spannenberg, Anke; Werner, Thomas (ACS Sustainable Chemistry & Engineering)
Keywords: T1; T2; CSSD

Chemoenzymatic Synthesis of Chiral Building Blocks Based on the Kinetic Resolution of Glycerol‐Derived Cyclic Carbonates - Terazzi, Constanza; Spannenberg, Anke; von Langermann, Jan; Werner, Thomas (ChemCatChem)
Abstract The biocatalytic kinetic resolution of cyclic carbonates derived from glycerol is reported. A selection of 26 esterases and lipases was tested for the asymmetric hydrolysis of the model substrate (epichlorohydrin carbonate) in aqueous medium. Among them, Pig Liver Esterase and Novozym® 435 showed the best selectivity with E =38 and 49, respectively. Both enzymes were employed for the conversion of 12 glycerol derivatives under optimized conditions. The resolution of halogenated carbonates afforded the unconverted enantiomer in up to >99 : 1 er . Furthermore, Novozym® 435 was successfully recycled 10 times without significant loss of activity. Upscaling and isolation of the chiral carbonate was also demonstrated. Subsequent conversion of this chiral building block allowed the direct one‐pot synthesis of ( S )‐Guaifenesin, ( S )‐Mephenesin and ( S )‐Chlorphenesin in up to 89 % yield and 94 : 6 er .
Keywords: T1; T4; CSSD

Synthesis of Cyclic Carbonates Catalyzed by CaI2–Et3N and Studies on Their Biocatalytic Kinetic Resolution - Terazzi, Constanza; Laatz, Karoline; von Langermann, Jan; Werner, Thomas (ACS Sustainable Chemistry and Engineering)
Keywords: T1; T3; CSSD

Synthesis of Bifunctional Phosphonium Salts Bearing Perfluorinated Side Chains and Their Application in the Synthesis of Cyclic Carbonates from Epoxides and CO 2 - Ren, Changyue; Spannenberg, Anke; Werner, Thomas (Asian Journal of Organic Chemistry)
Keywords: T1; T2; CSSD

Catalytic, Kinetic, and Mechanistic Insights into the Fixation of CO2 with Epoxides Catalyzed by Phenol‐Functionalized Phosphonium Salts - Hu, Yuya; Wei, Zhihong; Frey, Anna; Kubis, Christoph; Ren, Chang‐Yue; Spannenberg, Anke; Jiao, Haijun; Werner, Thomas (ChemSusChem)
Keywords: T1

Indirect reduction of CO2 and recycling of polymers by manganese-catalyzed transfer hydrogenation of amides, carbamates, urea derivatives, and polyurethanes - Liu, Xin; Werner, Thomas (Chemical Science)
A Mn–PNP complex proved to be a suitable catalyst for the transfer hydrogenation of amides, carbamates, urea derivatives and even polyurethanes.
Keywords: T1; T3; CSSD

Selective Construction of C−C and C=C Bonds by Manganese Catalyzed Coupling of Alcohols with Phosphorus Ylides - Liu, Xin; Werner, Thomas (Advanced Synthesis and Catalysis)
Keywords: T1; T3; CSSD

Catalytic Systems for the Synthesis of Biscarbonates and Their Impact on the Sequential Preparation of Non-Isocyanate Polyurethanes - Wulf, Christoph; Reckers, Matthias; Perechodjuk, Anna; Werner, Thomas (ACS Sustainable Chemistry and Engineering)
Keywords: T1; T3; CSSD

Plasma‐Assisted Immobilization of a Phosphonium Salt and Its Use as a Catalyst in the Valorization of CO 2 - Hu, Yuya; Peglow, Sandra; Longwitz, Lars; Frank, Marcus; Epping, Jan Dirk; Brüser, Volker; Werner, Thomas (ChemSusChem)
Keywords: T2; T1; CSSD

Life Cycle Assessment for the Organocatalytic Synthesis of Glycerol Carbonate Methacrylate - Büttner, Hendrik; Kohrt, Christina; Wulf, Christoph; Schäffner, Benjamin; Groenke, Karsten; Hu, Yuya; Kruse, Daniela; Werner, Thomas (ChemSusChem)
Keywords: T1; T4; CSSD

Polyethers as Complexing Agents in Calcium-Catalyzed Cyclic Carbonate Synthesis - Hu, Yuya; Steinbauer, Johannes; Stefanow, Vivian; Spannenberg, Anke; Werner, Thomas (ACS Sustainable Chemistry and Engineering)
Keywords: T1; T3; CSSD

Mechanistic Study on the Addition of CO2 to Epoxides Catalyzed by Ammonium and Phosphonium Salts: A Combined Spectroscopic and Kinetic Approach - Steinbauer, Johannes; Kubis, Christoph; Ludwig, Ralf; Werner, Thomas (ACS Sustainable Chemistry and Engineering)
Keywords: T1; T2; CSSD

Copolymerization of CO2 and epoxides mediated by zinc organyls - Wulf, Christoph; Doering, Ulrike; Werner, Thomas (RSC Advances)
Simple zinc organyls (R2Zn) efficiently catalyze the copolymerization of CO2 and cyclohexene oxide. The effect of various reaction parameters has been studied. The reaction proceeds under halogen-free conditions and no co-catalyst is required.
Keywords: T1; T3; CSSD

Calcium-Based Catalytic System for the Synthesis of Bio-Derived Cyclic Carbonates under Mild Conditions - Longwitz, Lars; Steinbauer, Johannes; Spannenberg, Anke; Werner, Thomas (ACS Catalysis)
Keywords: T1; T3; T4; CSSD

Calcium-Based Catalytic System for the Synthesis of Bio-Derived Cyclic Carbonates under Mild Conditions - Longwitz, Lars; Steinbauer, Johannes; Spannenberg, Anke; Werner, Thomas (ACS Catalysis)
Keywords: T1; T3; T4

Immobilized bifunctional phosphonium salts as recyclable organocatalysts in the cycloaddition of CO2 and epoxides - Steinbauer, J.; Longwitz, L.; Frank, M.; Epping, J.; Kragl, U.; Werner, Thomas (Green Chemistry)
An immobilized bifunctional phosphonium salt catalyst efficiently catalyzed the synthesis of cyclic carbonates under mild conditions, and was reused up to 15 times.
Keywords: T1; T2; CSSD

An in situ formed Ca2+–crown ether complex and its use in CO2-fixation reactions with terminal and internal epoxides - Steinbauer, J.; Spannenberg, A.; Werner, Thomas (Green Chemistry)
Calcium punched beyond its weight: An in situ formed Ca2+–crown ether complex showed unprecedented efficiency in cyclic carbonate synthesis.
Keywords: T1; T3; CSSD

Recent Developments in the Synthesis of Cyclic Carbonates from Epoxides and CO2 - Büttner, Hendrik; Longwitz, Lars; Steinbauer, Johannes; Wulf, Christoph; Werner, Thomas (Topics in Current Chemistry)
Keywords: T1; CSSD

Organocatalyzed Synthesis of Oleochemical Carbonates from CO2and Renewables - Büttner, Hendrik; Steinbauer, Johannes; Wulf, Christoph; Dindaroglu, Mehmet; Schmalz, Hans-Günther; Werner, Thomas (ChemSusChem)
Keywords: T1; T2; CSSD